Teaching Banned Books : 12 Guides for Young Readers. - Scales, Pat R. (ALA Editions, 2001)
Who hasn't read Blubber? And yet, published in 1974 and a New York Times 'Outstanding Book', it remains one of the 100 Most Frequently Challenged Books and is kept out of many school libraries. As a standard-bearer for intellectual freedom, the school librarian is in an ideal position to collaborate with teachers to not only protect the freedom to read but also ensure that valued books with valuable lessons are not quarantined from the readers for whom they were written. In this classroom- and library-ready book of discussion guides, award-winning champion of children's literature Pat Scales s.